2018
DOI: 10.1371/journal.pone.0201769
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a highly sensitive rapid diagnostic test (HS-RDT) for detecting malaria in peripheral and placental blood samples from pregnant women in Colombia

Abstract: BackgroundPregnancy poses specific challenges for the diagnosis of Plasmodium falciparum infection due to parasite sequestration in the placenta, which translates in low circulation levels in peripheral blood. The aim of this study is to assess the performance of a new highly sensitive rapid diagnostic test (HS-RDT) for the detection of malaria in peripheral and placental blood samples from pregnant women in Colombia.MethodsThis is a retrospective study using 737 peripheral and placental specimens collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
45
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 33 publications
6
45
1
2
Order By: Relevance
“…These results are supported by a study in Colombia, which also used stored samples from pregnant women. Although they note a trend of increased sensitivity by the uRDT, it was not found to be significantly different from the Standard Bioline RDT (sdRDT) [20]. A Tanzanian study in febrile children and adult outpatients also found no difference between uRDT and sdRDT performance, although febrile patients tend to have higher parasitaemia [29].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These results are supported by a study in Colombia, which also used stored samples from pregnant women. Although they note a trend of increased sensitivity by the uRDT, it was not found to be significantly different from the Standard Bioline RDT (sdRDT) [20]. A Tanzanian study in febrile children and adult outpatients also found no difference between uRDT and sdRDT performance, although febrile patients tend to have higher parasitaemia [29].…”
Section: Discussionmentioning
confidence: 93%
“…The only study in pregnant women did not observe notable differences in sensitivity between the uRDT and existing SD Bioline RDTs. [20].…”
Section: Introductionmentioning
confidence: 99%
“…In low malaria transmission settings, where both symptomatic and asymptomatic patients should be identified and treated, the conventional RDTs miss important proportions of infections. New combination, highly sensitive RDTs able to identify all infected individuals, will support countries implementing active case detection strategies,20 but their use and added benefit for malaria case management in pregnancy will need to be assessed 21. The high maternal mortality ratio (437/100 000) and perinatal mortality rate (39.3/1000) observed in the study cohort suggest that the risk factors for adverse birth outcomes in this community are multifactorial, including a weak health system.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, currently malaria diagnosis is mainly based on light microscopy (LM) and rapid diagnostic tests (RDTs); however, those tools, even though very useful, have some limitations in the elimination context. Recently, highly sensitive RDTs (HS-RDTs) have been developed and have been shown to improve performance in detecting low-density infections compared to LM or RDTs [6][7][8]. Nevertheless, more sensitive diagnostic tools may be required to detect transmissible very low parasites densities [9][10][11], and the emergence and spread of parasite with HRP2/3 deletion could definitely compromise the use of this new HS-RDT in some settings [12,13].…”
Section: Introductionmentioning
confidence: 99%